The multi-sensitive ion-imprinted polymer as a selective absorbent for the separation of ruthenium - Ting Huo; Xiaoyan Zhang; Hui Li; Xiaoqing Yu; Zhenbin Chen (Results in Surfaces and Interfaces, 2024)
In this study, a multi-sensitive ion-imprinted polymer that serves as a highly selective absorption material for ruthenium (Ru(III)) in complicated solutions was designed and prepared with the adoption of Pickering High Internal Phase Emulsions (HIPEs) polymerization technology. Meawhile, acrylamide (AM) and acrylic acid (AA) were used as functional monomers, Ru(III) as template ion, ethylene glycol dimethacrylate (EGDMA) as cross-linking agent and the redox system ammonium persulfate-N,N,N′,N′-tetramethylethylenediamine (AP-TEMED) as initiator for the synthesis of a smart ruthenium ion-imprinted polymer (Ru(III)–SIIP). The chemical structure, morphology and magnetic properties of Ru(III)–SIIP were characterized and subsequently used for the selective adsorption of Ru(III). The results revealed that Ru(III)–SIIP had obvious temperature sensitivity/pH sensitivity/magnetic sensitivity. The maximum adsorption capacity of Ru(III) was 0.191 mmol/g and coupled with a desorption ratio of 82.99%. The screening of the adsorption kinetics of Ru(III)–SIIP indicated that the zero-order and pseudo-first-order kinetic mixed model was more suitable for describing the adsorption process, while the Langmuir model was suitable for describing the isotherm of Ru(III)–SIIP. Furthermore, an adsorption method combined with inductively coupled plasma atomic emission spectrometry (ICP-AES) based on Ru(III)–SIIP was established for Ru(III) and successfully applied in the detection of Ru(III) in mixed solutions. To conclude, Ru(III)–SIIP has broad prospects for the recovery of ruthenium in complex environmental situations.